Kolomiets L. V. Models of author’s metaphors (by Pavlo Tychyna in Michael Naydan’s translation) - Kolomiets L. V. (Philological Treatises, 2020)
The article deals with the analysis of the author‟s metaphors by Pavlo Tychyna in Michael Naydan‟s Ukrainian–to–English translation. Seven possible modes of representing original metaphors in the target text, including neologisms, have been scrutinized.